ECLAC meeting the demand for statistics - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
ECLAC Economic Commission for Latin American Countries has established a statistical database on a wide variety of economic and social subjects for the CDCC countries of the Caribbean in recognition of the vital role played by statistics in the...